Integrating cardiovascular diseases, hypertension, and diabetes with HIV services: a systematic review - Haldane, V; Legido-Quigley, H; Chuah, FLH; Sigfrid, L; Murphy, G; Ong, SE; Cervero-Liceras, F; Watt, N; Balabanova, D; Hogarth, S; Maimaris, W; Buse, K; et al. (Taylor and Francis, 2017)
Non-communicable diseases (NCDs), including cardiovascular diseases (CVD), hypertension and diabetes together with HIV infection are among the major public health concerns worldwide. Health services for HIV and NCDs require health systems that provide for people’s chronic care needs, which present an opportunity to coordinate efforts and create synergies between programs to benefit people living with HIV and/or AIDS and NCDs. This review included studies that reported service integration for HIV and/or AIDS with coronary heart diseases, chronic CVD, cerebrovascular diseases (stroke), hypertension or diabetes. We searched multiple databases from inception until October 2015. Articles were screened independently by two reviewers and assessed for risk of bias. 11,057 records were identified with 7,616 after duplicate removal. After screening titles and abstracts, 14 papers addressing 17 distinct interventions met the inclusion criteria. We categorized integration models by diseases (HIV with diabetes, HIV with hypertension and diabetes, HIV with CVD and finally HIV with hypertension and CVD and diabetes). Models also looked at integration from micro (patient focused integration) to macro (system level integrations). Most reported integration of hypertension and diabetes with HIV and AIDS services and described multidisciplinary collaboration, shared protocols, and incorporating screening activities into community campaigns. Integration took place exclusively at the meso-level, with no micro- or macro-level integrations described. Most were descriptive studies, with one cohort study reporting evaluative outcomes. Several innovative initiatives were identified and studies showed that CVD and HIV service integration is feasible. Integration should build on existing protocols and use the community as a locus for advocacy and health services, while promoting multidisciplinary teams, including greater involvement of pharmacists. There is a need for robust and well-designed studies at all levels – particularly macro-level studies, research looking at long-term outcomes of integration, and research in a more diverse range of countries.